2007
DOI: 10.1002/ajmg.b.30581
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for interaction between MAOA and childhood adversity for antisocial behavior

Abstract: Previous reports have identified an interaction between an MAOA promoter polymorphism and childhood adversity for antisocial behavioral outcomes in males. This study attempted to replicate this finding in an Australian community survey of 1,002 Caucasian men aged 20-24 years. Greater childhood adversity was associated with later antisocial behavior, but no association was observed between MAOA genotype and antisocial behavior, and no interaction was found between childhood adversity and MAOA genotype for antis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 24 publications
1
38
0
2
Order By: Relevance
“…A significant reduced risk for conduct disorder was found among short-allele carriers by Foley et al, when adjusted for childhood adversity and interaction effects (Foley et al 2004). However, several studies have failed to find any main effect of the MAOA-VNTR (Haberstick et al 2005;Nilsson et al 2006;Prichard et al 2008;Widom and Brzustowicz 2006;Young et al 2006). A meta-analysis confirmed the presence of interaction effects between the MAOA-VNTR and childhood maltreatment in relation to problem behavior among boys (Kim-Cohen et al 2006).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A significant reduced risk for conduct disorder was found among short-allele carriers by Foley et al, when adjusted for childhood adversity and interaction effects (Foley et al 2004). However, several studies have failed to find any main effect of the MAOA-VNTR (Haberstick et al 2005;Nilsson et al 2006;Prichard et al 2008;Widom and Brzustowicz 2006;Young et al 2006). A meta-analysis confirmed the presence of interaction effects between the MAOA-VNTR and childhood maltreatment in relation to problem behavior among boys (Kim-Cohen et al 2006).…”
Section: Discussionmentioning
confidence: 87%
“…Since then, this finding has been replicated in at least four studies (Foley et al 2004;Kim-Cohen et al 2006;Nilsson et al 2006;Widom and Brzustowicz 2006). However, another study only found a non-significant trend in the same direction (Haberstick et al 2005), and in at least three further publications no significant interactions between childhood maltreatment and MAOA-VNTR in boys could be identified (Huizinga et al 2006;Prichard et al 2008;Young et al 2006). Our group previously reported that girls with the long (3.5 and 4 repeat) variant of the polymorphism are more likely to be involved in delinquent behavior in the presence of psychosocial risk ) and similar findings have recently been reported (PromWormley et al 2009).…”
Section: Introductionmentioning
confidence: 83%
“…For marker T102C (rs6313), the homozygous genotype CC showed an association with agitation and aggression in patients with Alzheimer disease (Lam et al 2004). However, Prichard et al (2008) failed to observe any significant association between this marker and a range of behaviors including psychosis, agitation, aberrant motor behavior, and depression. No association was found between rs6313 and suicidal behavior in normal subjects (Correa et al 2007), patients with schizophrenia (Ertugrul et al 2004), and suicide attempters (Zalsman et al 2005).…”
Section: Serotonin Receptorsmentioning
confidence: 85%
“…Most studies have focused on a single SNP providing a silent T102C polymorphism (rs6313) and have provided support for association with a range of behaviours, including psychosis, agitation, aberrant motor behaviour and depression (e.g. see Prichard et al 2008); however, these authors were unable to replicate a previous association reported for the CC genotype with agitation and aggression in Alzheimer's disease patients (Lam et al 2004). A second well-studied polymorphism is the G-1438A promoter SNP which is in nearly complete linkage disequilibrium with the silent T102C SNP has been examined in context of antisocial behaviours in alcohol dependents, and has been found to have signiWcant association with impulsive behaviour but not borderline or antisocial, personality disorders (Preuss et al 2001).…”
Section: Serotonin Receptorsmentioning
confidence: 99%